2014
DOI: 10.1053/j.ajkd.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Outcomes Between Continuous Ambulatory and Automated Peritoneal Dialysis: A Narrative Review

Abstract: Automated methods for delivering peritoneal dialysis (PD) to persons with end-stage renal disease continue to gain popularity worldwide, particularly in developed countries. However, the endeavor to automate the PD process has not been advanced on the strength of high-level evidence for superiority of automated over manual methods. This article summarizes available studies that have shed light on the evidence that compares the association of treatment with continuous ambulatory PD or automated PD (APD) with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 58 publications
1
63
0
1
Order By: Relevance
“…This question has been a recurrent matter of controversy [11] since first raised in the second half of the 1990s [7,8], with some observational studies disclosing differences [12,13] which other investigations have been unable to detect [14,15,16,17]. There are several potential explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This question has been a recurrent matter of controversy [11] since first raised in the second half of the 1990s [7,8], with some observational studies disclosing differences [12,13] which other investigations have been unable to detect [14,15,16,17]. There are several potential explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several small randomized trials [9,10] and observational studies [11] have provided controversial results. This question is consequential because a potential handicap of APD in this field could influence the current policy of many centers of starting patients directly on APD, according to their personal preference or to general QoL perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, accidental catheter disconnection during the night can be responsible for peritonitis, and recurrent ringing alarms that cannot be solved by the patient could lead to burn-out and transfer to HD. The cycler itself may also induce anxiety in older subjects that could affect their quality of life [17] and increase the risk of technique failure [18,19]. The role of the assistance modality (family or nurse-assisted PD) on both technique failure and peritonitis occurrence also needs to be explored.…”
Section: Impact Of Assisted Peritoneal Dialysis Modalitymentioning
confidence: 99%
“…A recent study suggested that PD results in higher P retention due to reduced clearance compared to HD [6]. This could be particularly true for patients treated with automated PD (APD) that has been reported to result in lower Na and P removal [7-9]. For Na, lower removal during APD can be explained by sodium sieving during the first hour of the dwell time due to transcellular water transport by aquaporins [10, 11].…”
Section: Introductionmentioning
confidence: 99%